2014
DOI: 10.1186/s13041-014-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Calretinin-positive L5a pyramidal neurons in the development of the paralemniscal pathway in the barrel cortex

Abstract: BackgroundThe rodent barrel cortex has been established as an ideal model for studying the development and plasticity of a neuronal circuit. The barrel cortex consists of barrel and septa columns, which receive various input signals through distinct pathways. The lemniscal pathway transmits whisker-specific signals to homologous barrel columns, and the paralemniscal pathway transmits multi-whisker signals to both barrel and septa columns. The integration of information from both lemniscal and paralemniscal pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Finally, Rorb labels locally connected excitatory interneurons of layer IV ( Jabaudon et al, 2012 ). Among Gad2 + cortical GABAergic interneurons, Sst and Calb2 mark specific subtypes ( Bartolini et al, 2013 ), although Calb2 has been shown to also be transiently expressed in pyramidal neurons residing in layer Va ( Liu et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Rorb labels locally connected excitatory interneurons of layer IV ( Jabaudon et al, 2012 ). Among Gad2 + cortical GABAergic interneurons, Sst and Calb2 mark specific subtypes ( Bartolini et al, 2013 ), although Calb2 has been shown to also be transiently expressed in pyramidal neurons residing in layer Va ( Liu et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since CR is expressed in several types of neurons, including cortical interneuron subtypes and pyramidal excitatory neurons in layer Vb (Liu et al 2014), we examined the ectopic CRpositive cells by double immunostaining for anti-CR and CTIP2, a specific marker for deeper layer excitatory neurons (Chen et al 2008). As shown in Figure 3A,B, none of the CR-positive cells co-expressed CTIP2, suggesting that the ectopic CRpositive cells were not excitatory neurons.…”
Section: The Ectopic Cr-positive Interneurons Were Generated Postnatallymentioning
confidence: 99%
“…Previously, we showed that CR is dynamically expressed in L5a pyramidal neurons in the developing barrel cortex and displays a unique predominantly serrated pattern that mirrors the presynaptic projection pattern of the posterior medial nucleus (Pom) to L5a [10,30]. In this study, by analyzing Cr KO mice, we found that loss of Cr results in a reduced complexity of L5a pyramidal neuron dendrites, which leads to abnormal formation of the barrel wall and subsequently impairs the barrel and septa microcircuits.…”
Section: Introductionmentioning
confidence: 63%